Marine Pollution - Monitoring, Management and Mitigation - Reichelt-Brushett, Amanda (Springer Textbooks in Earth Sciences, Geography and Environment,, 2023)
The study of marine environments inevitably involves considering the problem of marine pollution, which includes questions that focus on the essential need to ensure the long-term health of these exceptional ecosystems and the lives and livelihoods they support. The open access textbook "Marine Pollution: monitoring, management and mitigation" approaches these questions in a practical and highly readable format. It gives newcomers to the field background and perspective through the first comprehensive, multidisciplinary exploration of the topic. The topic is indeed complex, requiring the integration of the natural sciences and chemistry with management, policymakers, industry and all of us who are users of the marine environment. The textbook was written by leading experts to especially prepare graduates for a career in marine pollution studies. At the same time, it is relevant for anyone invested in the marine environment with a will to reduce their impacts. The chapters can easily be used independently and are also connected through the cross-referencing of related content. The introductory chapter provides a historical account of marine pollution and explores the fundamental physicochemical conditions of seawater. Two full chapters cover the requisite resources for ensuring success in field and laboratory studies. Then, chapter by chapter the book dives into to the various types of marine pollutants. In closing, it discusses the challenges of understanding multiple stressors and presents mitigation and restoration practices, along with a global overview of marine pollution legislation. We envisioned this textbook as being open access for the very reason we created it: this topic calls for global contributions and champions, and financial restraints should not limit access to this knowledge.